High-rate lithium nickel manganese oxide material modified by high-entropy doping site design, preparation method of high-rate lithium nickel manganese oxide material and lithium ion battery
Through the high-entropy doping site design method, a variety of doping elements are introduced into the nickel-manganate lithium material, which solves the problem of structural phase change and side reactions of the material during the charge and discharge cycle, and significantly improves the rate performance and cycling performance.
Patent Information
- Application Number
- CN202411862537.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
AI Technical Summary
During the charge and discharge cycle, lithium nickel manganate materials are prone to structural phase change and side reactions caused by the embedding and disengagement of lithium ions, resulting in a decrease in rate performance and rapid attenuation of capacity, limiting their commercial development and application.
The high-entropy doping site design method is adopted, and the site design doping regulation of two or more elements is carried out on the nickel and manganese positions, combined with the concept of high-entropy alloy, high-valent metal ions such as V5+/Nb5+/Sb5+/Mo6+ are added to improve the cation disorder of the material, and broaden the (110) crystal plane channels in the crystal structure that are conducive to ion diffusion.
The lithium ion diffusion coefficient of nickel-manganate material is significantly improved, the rate performance and cycling performance are enhanced, and the service life of the material is extended.
Smart Images

Figure CN119637958A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium nickel manganese oxide materials for lithium ion batteries, and in particular relates to a high-rate lithium nickel manganese oxide material with a high entropy doping site design and modification, a preparation method thereof, and a lithium ion battery. Background Art
[0002] In recent years, the process of comprehensive electrification has not only accelerated the development from hybrid vehicles to pure electric vehicles, but also promoted the innovation and improvement of related technologies. For new electric vehicle batteries, it involves many aspects of performance optimization, including energy density, charging and discharging speed, safety and cost-effectiveness. Compared with the current commercial lithium-ion battery nickel manganese oxide material, lithium iron phosphate has a low working voltage and is difficult to meet the needs; ternary lithium batteries are expensive, and cobalt elements are easily harmful to the human body and the environment. The working voltage of nickel manganese oxide material is as high as 4.7 V and has 690 Wh·kg −1 With its high energy density, low cost and stable safety performance, it has become a strong competitor for high energy density lithium-ion battery positive electrode materials in the future.
[0003] Lithium nickel manganese oxide material has three-dimensional ion diffusion channels, but due to its own structural influence, during the charge and discharge cycle, the insertion and extraction of lithium ions can easily lead to structural phase changes (Jahn-Teller effect) and serious side reactions (transition metal dissolution), which will lead to a decrease in its rate performance and rapid attenuation of capacity, restricting the further commercial development and application of lithium nickel manganese oxide materials.
[0004] At present, one method to inhibit the dissolution of transition metal ions in lithium nickel manganese oxide materials is to use ions of different valence states to dope the nickel and manganese sites in the spinel structure to achieve substitution at different sites in the lattice. + Mg 2+ , Cu 2+ 、Al 3+ Cr 3+ 、Ti 4+ 、V 5+ , Nb 5+ 、Mo 6+ However, due to the activity of these doping elements, the battery density decreases or safety issues occur to varying degrees. In addition, since the lithium nickel manganese oxide material itself has two structures, namely the ordered P4332 structure and the disordered Fd-3m structure. 2+ With Mn 4+ Randomly occupying the 16d position, that is, there is a phenomenon of mixed arrangement of nickel and manganese, which will be more conducive to the diffusion of lithium ions. However, in the process of doping modification, there are still great difficulties in studying the doping sites.
[0005] Although there are many ways of ion doping modification in the prior art, most of them use two or three multivalent transition metal elements to dope and replace the manganese element, and the improvement of material performance is limited. Summary of the invention
[0006] In order to solve the problems of decreased rate performance and rapid capacity decay of lithium nickel manganese oxide materials in the prior art and difficulty in determining doping sites during the modification process, the purpose of the present invention is to provide a high-rate lithium nickel manganese oxide material modified by high-entropy doping site design, a preparation method thereof and a lithium ion battery. The method is based on the concept of high entropy alloys and achieves targeted improvement of the crystal structure through doping site design, so that the lithium nickel manganese oxide has a higher lithium ion diffusion coefficient and has better rate performance and cycle performance.
[0007] To achieve the above object, the present invention is implemented through the following technical solutions: A method for preparing a high-rate lithium nickel manganese oxide material with a high entropy doping site design and modification, comprising the following steps: According to LiNi 0.5-x N x Mn 1.5-y M y O4 molar ratio, adding the lithium source, the nickel source and the manganese source into water to obtain a first solution; x ranges from 0.001 to 0.1, and y ranges from 0.001 to 0.1; Will be with Mn 4+ Soluble salts or metal oxides of the same or different valent dopant ions M with an ionic radius difference of 5 pm and Ni 2+ Soluble salts or metal oxides of N doped with the same or different valence ions with ionic radius difference of 5 pm, according to LiNi 0.5- x N x Mn 1.5-y M y O4 is added to the first solution at a molar ratio to obtain a second solution; adding a complexing agent and a viscosity modifier into the second solution to obtain a third solution; adjusting the pH value of the third solution to 4.5-5.5 to form a gel mixture; The gel mixture is aged, dried and then sintered to obtain a high entropy ion-doped spinel lithium nickel manganese oxide material.
[0008] Further, the lithium source is one or more of lithium acetate, lithium oxalate, lithium carbonate, lithium nitrate, lithium formate and lithium hydroxide; The manganese source is one or more of manganese acetate, manganese oxalate, manganese nitrate, manganese carbonate and manganese tetraoxide; The nickel source is one or more of nickel acetate, nickel oxalate, nickel nitrate, nickel carbonate and nickel hydroxide.
[0009] Furthermore, with Mn 4+ The same or different valent doping ions M with ionic radius difference of 5 pm represent Ti 4+ 、V 5+ , Nb 5+ , Sb 5 + with Mo 6+ One or more of the .
[0010] Furthermore, Ti 4+ Derived from at least one of titanium dioxide, titanium chloride, tetrabutyl titanate, tetraethyl titanate and titanyl sulfate; V 5+ Derived from at least one of ammonium metavanadate, lithium metavanadate, vanadium nitrate, vanadium pentoxide, vanadium hydroxide and vanadium pentachloride; Nb 5+ Derived from lithium niobate, niobium hydroxide, ammonium niobium oxalate, niobium nitrate or niobium pentoxide; Sb 5+ Derived from antimony pentoxide, antimony pentanate or antimony ammonium fluoride; Mo 6+ Derived from at least one of ammonium tetramolybdate, lithium molybdate and molybdenum trioxide.
[0011] Furthermore, with Ni 2+ Ion radii differing by 5 pm: N represents Mg 2+ , Cu 2+ With Al 3+ One or both of the following.
[0012] Furthermore, Mg 2+ Derived from magnesium acetate, magnesium nitrate, magnesium hydroxide or magnesium oxide; Cu 2+ Derived from at least one of copper acetate, copper nitrate, copper oxalate, copper chloride, copper sulfate, copper cyanide and copper acetylene; Al 3+ The aluminum oxide is derived from at least one of aluminum acetate, aluminum nitrate, lithium aluminate, aluminum hydroxide, aluminum oxide, aluminum silicate, aluminum chloride and alkyl aluminum.
[0013] Further, the complexing agent is at least one of ethylenediaminetetraacetic acid, citric acid, ethanolamine and acetylacetone; The ratio of the molar amount of the complexing agent, the total molar amount of all metal ions and the molar amount of the viscosity modifier is (0.95-2.25): 1:1; The viscosity modifier includes at least one of ethylene glycol, glycerol, polypropylene and carboxymethyl cellulose.
[0014] Use a sustained-release agent to adjust the pH.
[0015] Furthermore, the specific process of sintering is: heating up to the pre-firing temperature at a rate of 0.5 to 10°C / min, the pre-firing temperature is 450 to 550°C, the pre-firing time is 4 to 6 hours, then heating up to the sintering temperature at a rate of 0.5 to 10°C / min, the sintering temperature is 750 to 950°C, the sintering time is 8 to 15 hours, and cooling to room temperature at a rate of 0.5 to 2°C / min.
[0016] Furthermore, the sustained-release agent includes at least one of ammonia, acetic acid and carbonic acid enzyme. A high-rate lithium nickel manganese oxide material modified by high entropy doping site design.
[0017] A lithium ion battery comprises a positive electrode, a negative electrode and a separator between the positive electrode and the negative electrode, wherein the positive electrode is prepared by using the high-rate lithium nickel manganese oxide material modified by the high entropy doping site design.
[0018] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses a method for preparing a spinel nickel manganese oxide material with high entropy doping site design. By designing and doping two or more elements at the nickel and manganese sites, the rate performance and cycle performance of the lithium nickel manganese oxide are effectively improved. The present invention selects ions with similar atomic radii for different atomic sites for design replacement, thereby avoiding the generation of lattice distortion. Increasing V 5+ / Nb 5+ / Sb 5+ / Mo 6+ High-valent metal ions such as nickel and manganese can improve the cation disorder of the material and further improve the ionic conductivity and electronic conductivity of the crystal material. By designing the doping site, the (110) crystal plane channel in the crystal structure that is conducive to ion diffusion is broadened, greatly improving the transmission efficiency of lithium ions; this high-entropy doping method of designing the doping site for nickel and manganese plays an important role in improving the structure of lithium nickel manganese oxide and realizes the micro-control of the crystal structure. The lithium nickel manganese oxide modified material prepared by the present invention obtains a higher lithium ion diffusion coefficient and has better rate performance and cycle performance.
[0019] Furthermore, in the present invention, the complexing agent is used to form a stable complex with the metal ion through different coordination modes and chemical properties and by adjusting the pH of the system.
[0020] Furthermore, the viscosity modifier in the present invention improves gel stability and reduces hard agglomeration.
[0021] Furthermore, the sintering in the present invention is divided into two stages. First, the precursor material is heated at 450°C to remove impurities and eliminate local inhomogeneities. Second, it is uniformly heated at 850°C and crystallized to obtain a spinel structure with excellent crystallinity. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The charge and discharge curves of the electrodes prepared from the materials of Example 1 and Comparative Examples 1-3 at 0.1C; Figure 2 A comparison diagram of rate curves of electrodes prepared from materials of Example 1 and Comparative Examples 1-3; Figure 3 This is a SEM image of the material prepared in Example 1; Figure 4 The graph is a cycle performance diagram of the electrodes prepared in Example 1 and Comparative Examples 1-3 at a current density of 1C. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the present invention more clear, the following is further described in detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, not all embodiments.
[0024] The components described and shown in the drawings and embodiments of the present invention may be arranged and designed in various configurations. Therefore, the detailed description of the embodiments of the present invention provided in the following drawings is not intended to limit the scope of the claimed invention, but merely represents a selected embodiment of the present invention. Based on the drawings and embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0025] The present invention discloses a method for preparing a spinel nickel manganese oxide material modified by high entropy doping site design, comprising the following steps: S1. According to LiNi 0.5-x N x Mn 1.5-y M y The lithium source, nickel source and manganese source are added into 100 ml of deionized water in a molar ratio of O4, and stirred for 10 min to fully dissolve and evenly disperse them to obtain a first solution; the range of x is 0.001-0.1, and the range of y is 0.001-0.1; The lithium source is one or more of lithium acetate, lithium oxalate, lithium carbonate, lithium nitrate, lithium formate and lithium hydroxide; The nickel source is one or more of nickel acetate, nickel oxalate, nickel nitrate, nickel carbonate and nickel hydroxide; The manganese source is one or more of manganese acetate, manganese oxalate, manganese nitrate, manganese carbonate and manganese tetraoxide; S2, will be with Mn 4+ Ionic radius (R Mn4+ =53pm) is close to (i.e., with Mn 4+ Soluble salts or metal oxides of the same or different valent dopant ions M with an ionic radius difference of 5 pm and Ni 2+ Ionic radius (R Ni2+ = 69pm) of soluble salts or metal oxides of N doping ions of the same or different valence, according to LiNi 0.5-x N x Mn 1.5-y M y O4 is added to the first solution in a doping ratio and stirred for 10 min to fully dissolve and evenly disperse it to obtain a second solution; Since the doping process generally follows the lattice matching principle, that is, the ion radius, charge size and lattice structure of the doped ions should match the original lattice as much as possible to ensure that the doped ions can effectively replace the original ions and stably exist in the lattice to avoid lattice distortion or structural damage. 4+ Soluble salts or metal oxides of the same or different valent dopant ions M with similar ionic radius and Ni 2+ Soluble salts or metal oxides of N dopant ions of similar or opposite valence with similar ionic radius.
[0026] In step S2, the doping ions M in the manganese doping are 4+ Ion Ti with similar ionic radius 4 + 、V 5+ , Nb 5+ , Sb 5+ with Mo 6+ One or more of the following; Among them, Ti 4+ Derived from at least one of titanium dioxide, titanium chloride, tetrabutyl titanate, tetraethyl titanate and titanyl sulfate; V 5+ Derived from at least one of ammonium metavanadate, lithium metavanadate, vanadium nitrate, vanadium pentoxide, vanadium hydroxide and vanadium pentachloride; Nb 5+ Derived from lithium niobate, niobium hydroxide, ammonium niobium oxalate, niobium nitrate or niobium pentoxide; Sb 5+ Derived from antimony pentoxide, antimony pentanate or antimony ammonium fluoride; Mo 6+ Derived from at least one of ammonium tetramolybdate, lithium molybdate and molybdenum trioxide.
[0027] In step S2, the doping ions N in the nickel position represent the same 2+ Similar ionic radius (i.e., Ni 2+ Ionic or heterovalent ions of Mg with a difference of 5 pm in ionic radius 2+ , Cu 2+ With Al 3+ One or both of the following: Mg 2+ Derived from magnesium acetate, magnesium nitrate, magnesium hydroxide or magnesium oxide; Cu 2+ Derived from at least one of copper acetate, copper nitrate, copper oxalate, copper chloride, copper sulfate, copper cyanide and copper acetylene; Al 3+ Derived from at least one of aluminum acetate, aluminum nitrate, lithium aluminate, aluminum hydroxide, aluminum oxide, aluminum silicate, aluminum chloride and alkyl aluminum. The alkyl aluminum is triethyl aluminum, triisopropyl aluminum or diethyl aluminum chloride; S3, dissolving the complexing agent and the viscosity adjusting agent in the second solution in a certain proportion to obtain a third solution; The third solution is heated in a constant temperature water bath at 80-85° C., stirred, and the pH value of the system is adjusted to 4.5-5.5 with a sustained-release agent, and mixed and stirred to form a gel mixture.
[0028] The complexing agent includes at least one of ethylenediaminetetraacetic acid (EDTA), citric acid, ethanolamine and acetylacetone.
[0029] The viscosity modifier includes at least one of ethylene glycol, glycerol, polypropylene and carboxymethyl cellulose. The viscosity modifier improves gel stability and reduces hard agglomeration.
[0030] The sustained-release agent includes at least one of ammonia water, acetic acid and carbonic acid enzyme. In the gel-forming process, the complexing agent is used to form a stable complex with metal ions through different coordination modes and chemical properties and adjusting the pH of the system. The molar ratio of the molar amount of the complexing agent to the total molar amount of metal ions in the lithium nickel manganese oxide material satisfies (0.95-2.25): 1. The ratio of the complexing agent to the metal ions significantly affects the characteristics of the entire process and the final product.
[0031] S4. The gel mixture is aged and dried to obtain a black fluffy powder. The black fluffy powder is ground and calcined in a muffle furnace at 700° C.-900° C. in an air atmosphere for 8-15 hours to obtain a high entropy ion-doped spinel lithium nickel manganese oxide material.
[0032] The calcination is specifically divided into two stages, and the sintering conditions include: heating to the pre-firing temperature at a heating rate of 0.5 to 10°C / min, the pre-firing temperature is 450 to 550°C, and the constant temperature time at the pre-firing temperature is 4 to 6 hours; then heating to the sintering temperature at a heating rate of 0.5 to 10°C / min, the sintering temperature is 750 to 950°C, and the constant temperature time at the sintering temperature is 8 to 15 hours; finally, cooling to room temperature at a cooling rate of 0.5 to 2°C / min.
[0033] The spinel lithium manganese oxide material with high entropy doping site design and modification prepared by the present invention can be used as a nickel lithium manganese oxide material in lithium ion batteries.
[0034] like Figure 3 As shown, the ion doping used in the present invention increases the unit cell parameters, and the (110) crystal plane is greatly widened, providing the fastest transmission channel for lithium ion diffusion, thereby improving the rate performance of the material.
[0035] A high entropy doping site-designed modified spinel lithium nickel manganese oxide material prepared according to the above method comprises a lithium nickel manganese oxide material body and doping elements whose doping sites are designed in the lithium nickel manganese oxide material body include two or more of Cu, Al, Ti, V and Mo.
[0036] The features and performances of the present invention are further described in detail below in conjunction with the embodiments.
[0037] Example 1 S1. Design the doping site according to Li1.01Ni0.5-7 / 3xCuxAlxMn1.5-7 / 3yTiyVyO4, with the doping content x=0.01, y=0.01, weigh lithium acetate, nickel acetate and manganese acetate in corresponding proportions, dissolve the three raw materials in deionized water respectively, and obtain a first solution after fully dissolving at room temperature 25°C, then weigh copper acetate, aluminum nitrate, titanium dioxide and ammonium metavanadate according to the proportion, and fully dissolve them in the first solution to obtain a second solution; S2, according to the molar ratio of all metal ions: citric acid: ethylene glycol of 2:1:1, citric acid and ethylene glycol were added to the second solution in sequence, the temperature of the gel solution was controlled at 85°C by auxiliary heating, ammonia water was added dropwise to control the pH to 4.8, and stirring was continued for 6 hours to form a gel mixture; S3, aging and drying the gel mixture to obtain a black fluffy powder, grinding the black fluffy powder, first heating it to 450°C at a heating rate of 5°C / min in an air atmosphere in a muffle furnace for pre-sintering for 4h, then heating it to 800°C at a heating rate of 5°C / min for calcination for 12h, and cooling it to room temperature at a cooling rate of 2°C / min. After taking it out, grinding it thoroughly, sieving it through a 200-mesh sieve, and obtaining a spinel lithium manganese oxide material modified by a high entropy doping site design, that is, a Li1.01Ni0.47Cu0.01 Al0.01Mn1.47Ti0.01V0.01O4 spinel nickel lithium manganese oxide modified material with a site design of quaternary ions.
[0038] The present invention draws on the concept of high entropy alloys and is composed of five or more metal elements with a highly mixed crystal structure. The average standard molar entropy value of the doped elements is selected to be greater than the standard molar entropy value of the nickel and manganese elements they replace. The overall entropy value of the system is increased and the disorder is enhanced.
[0039] Example 2 S1. Design the doping site according to Li1.01Ni0.5-7 / 3xCuxAlxMn1.5-7 / 3yTiyVyO4, with the doping content x=0.005, y=0.005, weigh lithium acetate, nickel acetate and manganese acetate in corresponding proportions, dissolve the three raw materials in deionized water respectively, and obtain a first solution after fully dissolving at room temperature 25°C, then weigh copper acetate, aluminum nitrate, titanium dioxide and ammonium metavanadate according to the proportion, and fully dissolve them in the first solution to obtain a second solution; S2, according to the metal ion: citric acid: ethylene glycol metering ratio of 2:1:1, citric acid and ethylene glycol were added to the second solution in sequence, auxiliary heating was performed to control the temperature of the gel solution at 85°C, ammonia water was added dropwise to control the pH to 4.8, and stirring was continued for 6 hours to form a gel mixture; S3, the gel mixture is aged and dried to obtain a black fluffy powder, the black fluffy powder is ground, and then the temperature is raised to 450°C in an air atmosphere in a muffle furnace at a heating rate of 5°C / min for pre-sintering for 4h, and then the temperature is raised to 800°C at a heating rate of 5°C / min for calcination for 12h, and the temperature is cooled to room temperature at a cooling rate of 2°C / min. After taking out, it is fully ground and sieved through a 200-mesh sieve to obtain a spinel lithium manganese oxide material modified by a high entropy doping site design, that is, a quaternary ion doped Li1.01Ni0.48Cu0.005Al0.005Mn1.48Ti0.005V0.005O4 spinel nickel lithium manganese oxide modified material with a doping content of 0.5%.
[0040] As shown in Table 1, the quaternary ion modified doping material Li1.01Ni0.48Cu0.005Al0.005Mn1.48Ti0.005V0.005O4 prepared in Example 2 with a doping concentration of 0.5% has an initial discharge capacity of 121.3mAh / g at 0.1C, and a 20C fast charge and discharge capacity of 90.7mAh / g. The capacity is still 105.7mAh / g after long-term cycling at a current density of 1C.
[0041] Example 3 S1. Design the doping site according to Li1.01Ni0.5-1.5xCuxAlxMn1.5-1.5yTiyO4, with the doping content x=0.01, y=0.01, weigh lithium oxalate, nickel acetate, nickel carbonate and manganese nitrate in corresponding proportions in sequence, dissolve the raw materials in 100 ml of deionized water respectively, and fully dissolve them at room temperature of 25°C to obtain a first solution, then weigh copper acetate, aluminum nitrate and titanium dioxide according to the proportion, and fully dissolve them in the first solution to obtain a second solution; S2, adding ethylenediaminetetraacetic acid and glycerol to the second solution in a molar ratio of all metal ions: ethylenediaminetetraacetic acid: glycerol of 2:1:1, auxiliary heating to control the temperature of the gel solution at 85°C, adding ammonia water to control the pH to 4.5, and stirring for 6 hours to form a gel mixture; S3, aging and drying the gel mixture to obtain a black fluffy powder, grinding the black fluffy powder, first heating it to 450°C in an air atmosphere in a muffle furnace at a heating rate of 0.5°C / min for pre-sintering for 6 hours, then heating it to 950°C at a heating rate of 0.5°C / min for calcination for 8 hours, and cooling it to room temperature at a cooling rate of 0.5°C / min. After taking it out, grinding it thoroughly, sieving it through a 200-mesh sieve, and obtaining a spinel lithium manganese oxide material with a high entropy doping site design modification.
[0042] The modified material Li1.01Ni0.485Cu0.01Al0.01Mn1.485Ti0.01O4 prepared in Example 3 has an initial discharge capacity of 134.6 mAh / g at 0.1C, and a 30C fast charge and discharge capacity of 92.2 mAh / g. After long-term cycling at 1C current density, the capacity is still 118.5 mAh / g.
[0043] Example 4 S1. According to Li1.01Ni0.5-10 / 3xCuxAlxMn1.5-10 / 3yTiyVyMoyO4, the doping site is designed, and the doping content x=0.01, y=0.01, lithium carbonate, nickel hydroxide and manganese oxalate in corresponding proportions are weighed in sequence, and the raw materials are dissolved in 100 ml of deionized water respectively. After fully dissolved at room temperature of 25°C, a first solution is obtained, and then copper acetate, aluminum nitrate, titanium dioxide, vanadium pentoxide and ammonium tetramolybdate are weighed in proportion, and fully dissolved in the first solution to obtain a second solution; S2, adding ethanolamine and polypropylene to the second solution in sequence according to the molar ratio of all metal ions: ethanolamine: polypropylene of 2:1:1, auxiliary heating to control the temperature of the gel solution at 80°C, adding ammonia water dropwise to control the pH to 4.8, and stirring for 6 hours to form a gel mixture; S3, aging and drying the gel mixture to obtain a black fluffy powder, grinding the black fluffy powder, first heating the temperature to 500°C at a heating rate of 10°C / min in an air atmosphere in a muffle furnace for pre-sintering for 5 hours, then heating the temperature to 800°C at a heating rate of 10°C / min for calcination for 13 hours, and cooling the temperature to room temperature at a cooling rate of 1°C / min. After taking out, grinding it thoroughly, sieving it through a 200-mesh sieve, and obtaining a spinel lithium manganese oxide material with a high entropy doping site design modification.
[0044] The modified material Li1.01Ni0.467Cu0.01Al0.01Mn1.467Ti0.01V0.01Mo0.01O4 prepared in Example 4 has an initial discharge capacity of 130.7 mAh / g at 0.1C, and a 30C fast charge and discharge capacity of 91.7 mAh / g. After long-term cycling at 1C current density, the capacity is still 117.3 mAh / g. Compared with Example 1, the increase of doping elements does not further improve the rate and cycle performance of the material. Example 5 S1. Design the doping site according to Li1.01Ni0.5-7 / 3xCuxAlxMn1.5-7 / 3yTiyVyO4, with the doping content x=0.0001, y=0.001, weigh lithium nitrate, nickel carbonate and manganese nitrate in corresponding proportions in turn, dissolve the raw materials in 100 ml of deionized water respectively, and fully dissolve them at room temperature of 25°C to obtain a first solution, then weigh copper acetate, aluminum nitrate, titanium dioxide and ammonium metavanadate according to the proportion, and fully dissolve them in the first solution to obtain a second solution; S2, according to the molar ratio of all metal ions: acetylacetone: carboxymethyl cellulose of 0.95:1:1, acetylacetone and carboxymethyl cellulose were added to the second solution in sequence, the temperature of the gel solution was controlled at 83°C by auxiliary heating, acetic acid was added dropwise to control the pH to 5.5, and stirring was continued for 6 hours to form a gel mixture; S3, aging and drying the gel mixture to obtain a black fluffy powder, grinding the black fluffy powder, first heating it to 550°C in an air atmosphere in a muffle furnace at a heating rate of 2°C / min for pre-sintering for 4 hours, then heating it to 750°C at a heating rate of 2°C / min for calcination for 15 hours, and cooling it to room temperature at a cooling rate of 2°C / min. After taking it out, grinding it thoroughly, sieving it through a 200-mesh sieve, and obtaining a spinel lithium manganese oxide material with a high entropy doping site design modification.
[0045] Example 6 S1. Design the doping site according to Li1.01Ni0.5-7 / 3xCuxAlxMn1.5-7 / 3yTiyVyO4, with the doping content x=0.1, y=0.1, weigh lithium formate, nickel nitrate and nickel carbonate in corresponding proportions in turn, dissolve the raw materials in 100 ml of deionized water respectively, and fully dissolve them at room temperature of 25°C to obtain a first solution, then weigh copper acetate, aluminum nitrate, titanium dioxide and ammonium metavanadate according to the proportion, and fully dissolve them in the first solution to obtain a second solution; S2, according to the molar ratio of all metal ions: mixture of citric acid and ethylenediaminetetraacetic acid: ethylene glycol of 2.25:1:1, add the mixture of citric acid and ethylenediaminetetraacetic acid and ethylene glycol to the second solution in sequence, auxiliary heating to control the temperature of the gel solution at 82°C, add ammonia water dropwise to control the pH to 5, and continue stirring for 6 hours to form a gel mixture; S3, aging and drying the gel mixture to obtain a black fluffy powder, grinding the black fluffy powder, first heating it to 520°C in an air atmosphere in a muffle furnace at a heating rate of 5°C / min for pre-sintering for 5h, then heating it to 900°C at a heating rate of 5°C / min for calcination for 10h, and cooling it to room temperature at a cooling rate of 1.5°C / min. After taking it out, grinding it thoroughly, sieving it through a 200-mesh sieve, and obtaining a spinel lithium manganese oxide material with a high entropy doping site design modification.
[0046] Example 7 S1. Design the doping site according to Li1.01Ni0.5-7 / 3xCuxAlxMn1.5-7 / 3yTiyVyO4, with the doping content x=0.05, y=0.05, weigh lithium formate, lithium hydroxide, nickel oxalate, manganese acetate and manganese tetraoxide in corresponding proportions, dissolve the raw materials in 100 ml of deionized water respectively, and fully dissolve them at room temperature of 25°C to obtain a first solution, then weigh copper acetate, aluminum nitrate, titanium dioxide and ammonium metavanadate according to the proportion, and fully dissolve them in the first solution to obtain a second solution; S2, according to the molar ratio of all metal ions: citric acid: the mixture of ethylene glycol and glycerol of 1:1:1, citric acid and the mixture of ethylene glycol and glycerol are added to the second solution in sequence, auxiliary heating is performed to control the temperature of the gel solution at 85°C, and a carbonic acid enzyme aqueous solution is added to control the pH to 4.2, and stirring is continued for 6 hours to form a gel mixture; S3, aging and drying the gel mixture to obtain a black fluffy powder, grinding the black fluffy powder, first heating it to 470°C in an air atmosphere in a muffle furnace at a heating rate of 8°C / min for pre-sintering for 5h, then heating it to 850°C at a heating rate of 8°C / min for calcination for 12h, and cooling it to room temperature at a cooling rate of 2°C / min. After taking it out, grinding it thoroughly, sieving it through a 200-mesh sieve, and obtaining a spinel lithium manganese oxide material with a high entropy doping site design modification.
[0047] Comparative Example 1 S1. Weigh lithium acetate, nickel acetate and manganese acetate according to the Li:Ni:Mn element ratio of 1.01:0.5:1.5, dissolve the three raw materials in deionized water respectively, and fully dissolve them at room temperature of 25°C; S2, adding citric acid and ethylene glycol in the metal ion: citric acid: ethylene glycol ratio of 2:1:1, auxiliary heating to control the temperature of the gel solution at 85°C, adding ammonia water to control the pH to 4.8, and stirring for 6 hours to form a gel mixture; S3. The gel mixture is aged and dried to obtain a black fluffy powder. The black fluffy powder is ground and pre-sintered at 450° C. for 4 h in an air atmosphere in a muffle furnace, and then calcined at 800° C. for 12 h. After being taken out, the powder is fully ground and sieved through a 200-mesh sieve to obtain an undoped Li1.01Ni0.5Mn1.5O4 spinel nickel manganese oxide pure phase material.
[0048] The electrochemical test method of this product is the same as that of Example 1, and the 0.1C electrochemical performance test results and rate and cycle performance are shown in Table 1. Compared with the pure phase lithium nickel manganese oxide material, the 30C high rate charge and discharge performance of Example 1 modified by CATV high entropy doping is significantly enhanced.
[0049] Comparative Example 2 S1. Mix nickel and manganese positions according to Li1.01Ni0.5-XMn1.5-xCuxAlxO4, without designing specific doping sites, with a doping content of X=1%. Sequentially weigh lithium acetate, nickel acetate, and manganese acetate in corresponding proportions, dissolve the three raw materials in deionized water, and fully dissolve them at room temperature of 25°C. Then weigh copper acetate and aluminum nitrate according to the proportions and fully dissolve them in the solution. S2, adding citric acid and ethylene glycol in the metal ion: citric acid: ethylene glycol ratio of 2:1:1, auxiliary heating to control the temperature of the gel solution at 85°C, adding ammonia water to control the pH to 4.8, and stirring for 6 hours to form a gel mixture; S3. The gel mixture is aged and dried to obtain a black fluffy powder. The black fluffy powder is ground and pre-sintered at 450° C. for 4 h in an air atmosphere in a muffle furnace, and then calcined at 800° C. for 12 h. After being taken out, the powder is fully ground and sieved through a 200-mesh sieve to obtain a mixed-doped Li1.01Ni0.49Mn1.49Cu0.01Al0.01O4 spinel nickel manganese oxide modified material without a specific doping site design.
[0050] Comparative Example 3 S1. Mix nickel and manganese positions according to Li1.01Ni0.5-2xMn1.5-2xCuxAlxTixVxO4, without designing specific doping sites, with a doping content of X=1%. Sequentially weigh lithium acetate, nickel acetate, and manganese acetate in corresponding proportions, dissolve the three raw materials in deionized water, and fully dissolve them at room temperature of 25°C. Then weigh copper acetate, aluminum nitrate, titanium dioxide, and ammonium metavanadate in proportion and fully dissolve them in the solution. S2, adding citric acid and ethylene glycol in the metal ion: citric acid: ethylene glycol ratio of 2:1:1, auxiliary heating to control the temperature of the gel solution at 85°C, adding ammonia water to control the pH to 4.8, and stirring for 6 hours to form a gel mixture; S3. The gel mixture is aged and dried to obtain a black fluffy powder. The black fluffy powder is ground and pre-sintered at 450°C for 4 hours in an air atmosphere in a muffle furnace, and then calcined at 800°C for 12 hours. After being taken out, it is fully ground and sieved through a 200-mesh sieve to obtain a mixed-doped Li1.01Ni0.48Mn1.48Cu0.01Al0.01Ti0.01V0.01O4 spinel nickel manganese oxide modified material without designed specific doping sites.
[0051] The electrochemical testing method of the modified lithium nickel manganese oxide material of the present invention is the same as that of Example 1. The 0.1C electrochemical performance test results and the rate and cycle performance are shown in Table 1, where the rate performance is compared with that of Comparative Example 1.
[0052] The charge and discharge performance test of the products obtained in all embodiments and comparative examples was carried out according to the following method: the prepared materials were crushed, ground and sieved, and then mixed with acetylene black and PVDF in a mass ratio of 8:1:1, and added to N-methylpyrrolidone solvent; the ground uniform slurry was coated on aluminum foil and dried at 120°C for 12h to obtain a positive electrode sheet. A 2016 buckle battery was assembled in a glove box with a lithium sheet as the negative electrode, a PE film as the diaphragm, and LiPF6 as the electrolyte. The electrochemical test was carried out with constant current charge and discharge, and the voltage range was 3.5V-4.9V (0.1C=146.7mAh / g) after 5 cycles of 1C cycle, and the room temperature test temperature was 25°C. The electrochemical test method of the obtained product is the same as that of Example 1, and its 0.1C electrochemical performance test results, rate and cycle performance are shown in Table 1.
[0053] Table 1 0.1C first discharge capacity, rate and cycle performance of the electrode materials obtained in each example
[0054] From Example 1 and three Comparative Examples 1-3, it can be clearly concluded that Comparative Example 1 represents an undoped pure phase lithium nickel manganese oxide material, Comparative Example 2 represents a sample doped with two elements of Cu and Al in nickel and manganese without doping site design, and Comparative Example 3 represents a sample doped with four elements of Cu, Al, Ti, and V in nickel and manganese without doping site design. Analysis and research show that the specific capacity of Example 1, Comparative Examples 2 and Comparative Examples 3 at 30C is higher than that of Comparative Example 1, among which Example 1 with doping site design shows the best rate performance. In addition, the capacity of Example 1 after 300 cycles at 1C is higher than that of Comparative Example 1 by ~10 mAh / g.
[0055] like Figure 1 As shown, the charge and discharge curves of the prepared electrode at 0.1C indicate that the sample with high entropy ion doping site design on the nickel manganese oxide material (Example 1) has some influence on the initial discharge specific capacity of the material. This is attributed to the targeted entry of the doping elements into the positions of nickel and manganese and the corresponding doping ratio, which is beneficial to increase the lithium ion diffusion rate and help lithium ion deintercalation.
[0056] like Figure 2 As shown in the figure, the rate curves of the obtained electrode materials are compared. The charge and discharge behavior at a current density of 30C shows that the discharge capacity of the lithium nickel manganese oxide modified sample designed with high entropy doping sites is ~60 mAh / g higher than that of the original sample. Figure 3As shown in the analysis, the spinel-like nickel manganese oxide lithium material has a significantly increased (110) crystal plane ratio due to the targeted addition of four doping elements in Example 1. Since the (110) plane is perpendicular to the Li ion diffusion channel, its migration path is the shortest and has the fastest lithium ion transmission rate. Properly increasing the (110) crystal plane ratio helps to improve the rate performance of the material. In addition, it is worth mentioning that the current density of charging and discharging in the test rate performance of the present invention both reaches 30C. Therefore, the method provided by the present invention can not only greatly improve the rate performance of the material, but also realize the rapid charging and discharging behavior of the electrode material. like Figure 4 As shown, the cycling performance of the prepared electrode material at a current density of 1C; Example 1 exhibits excellent cycling stability, and the capacity is still 121.7 mAh / g after 300 cycles from the initial 134.4 mAh / g, with a retention rate of up to 90.55%; this is mainly due to the fact that the doping site design effectively improves the structural stability of the spinel.
[0057] The present invention is based on the concept of high entropy alloys and factors such as charge state balance and ion radius matching, comprehensively considers the changes in the electronic structure and band structure of the material, uses copper (Cu), aluminum (Al), titanium (Ti), vanadium (V) and molybdenum (Mo) as multiple metal doping elements, and designs doping sites through sol-gel method or coprecipitation method, thereby realizing micro-control of the crystal structure of the material and enhancing the electronic conductivity and ionic conductivity of the material. The modified lithium nickel manganese oxide material not only has excellent structural stability, but also has significantly improved specific capacity under 30C high-rate fast charging. This method has the advantages of simple operation, high efficiency, low energy consumption, and environmental friendliness. The prepared modified lithium nickel manganese oxide material has the characteristics of strong stability, reliable performance, and easy industrial production. Finally, the modified lithium nickel manganese oxide material can significantly improve the electrochemical performance of the battery and is suitable for manufacturing various high-performance batteries.
[0058] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0059] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing a high-rate lithium nickel manganese oxide material with a high entropy doping site design and modification, characterized in that: The following steps are involved: According to LiNi 0.5-x N x Mn 1.5-y M y O4 molar ratio, adding the lithium source, the nickel source and the manganese source into water to obtain a first solution; x ranges from 0.001 to 0.1, and y ranges from 0.001 to 0.1; Will be with Mn 4+ Soluble salts or metal oxides of the same or different valent dopant ions M with an ionic radius difference of 5 pm and Ni 2+ Soluble salts or metal oxides of N doped with the same or different valence ions with ionic radius difference of 5 pm, according to LiNi 0.5- x N x Mn 1.5-y M y O4 is added to the first solution at a molar ratio to obtain a second solution; adding a complexing agent and a viscosity modifier into the second solution to obtain a third solution; adjusting the pH value of the third solution to 4.5-5.5 to form a gel mixture; The gel mixture is aged, dried and then sintered to obtain a high entropy ion-doped spinel lithium nickel manganese oxide material.
2. The method for preparing the high-rate lithium nickel manganese oxide material with high entropy doping site design and modification according to claim 1, characterized in that: The lithium source is one or more of lithium acetate, lithium oxalate, lithium carbonate, lithium nitrate, lithium formate and lithium hydroxide; The manganese source is one or more of manganese acetate, manganese oxalate, manganese nitrate, manganese carbonate and manganese tetraoxide; The nickel source is one or more of nickel acetate, nickel oxalate, nickel nitrate, nickel carbonate and nickel hydroxide.
3. The method for preparing the high-rate lithium nickel manganese oxide material with high entropy doping site design and modification according to claim 1, characterized in that: With Mn 4+ The same or different valent doping ions M with ionic radius difference of 5 pm represent Ti 4+ 、V 5+ , Nb 5+ , Sb 5+ with Mo 6+ One or more of the .
4. The method for preparing the high-rate lithium nickel manganese oxide material with high entropy doping site design and modification according to claim 3, characterized in that: Ti 4+ Derived from at least one of titanium dioxide, titanium chloride, tetrabutyl titanate, tetraethyl titanate and titanyl sulfate; V 5+ Derived from at least one of ammonium metavanadate, lithium metavanadate, vanadium nitrate, vanadium pentoxide, vanadium hydroxide and vanadium pentachloride; Nb 5+ Derived from lithium niobate, niobium hydroxide, ammonium niobium oxalate, niobium nitrate or niobium pentoxide; Sb 5+ Derived from antimony pentoxide, antimony pentanate or antimony ammonium fluoride; Mo 6+ Derived from at least one of ammonium tetramolybdate, lithium molybdate and molybdenum trioxide.
5. The method for preparing the high-rate lithium nickel manganese oxide material with high entropy doping site design and modification according to claim 1, characterized in that: with Ni 2+ Ion radii differing by 5 pm: N represents Mg 2+ , Cu 2+ With Al 3+ One or both of the following.
6. The method for preparing the high-rate lithium nickel manganese oxide material with high entropy doping site design and modification according to claim 5, characterized in that: Mg 2+ Derived from magnesium acetate, magnesium nitrate, magnesium hydroxide or magnesium oxide; Cu 2+ Derived from at least one of copper acetate, copper nitrate, copper oxalate, copper chloride, copper sulfate, copper cyanide and copper acetylene; Al 3+ The aluminum oxide is derived from at least one of aluminum acetate, aluminum nitrate, lithium aluminate, aluminum hydroxide, aluminum oxide, aluminum silicate, aluminum chloride and alkyl aluminum.
7. The method for preparing the high-rate lithium nickel manganese oxide material with high entropy doping site design and modification according to claim 1, characterized in that: The complexing agent is at least one of ethylenediaminetetraacetic acid, citric acid, ethanolamine and acetylacetone; The ratio of the molar amount of the complexing agent, the total molar amount of all metal ions and the molar amount of the viscosity modifier is (0.95~2.25): 1:1; The viscosity modifier includes at least one of ethylene glycol, glycerol, polypropylene and carboxymethyl cellulose; Use a sustained-release agent to adjust the pH.
8. The method for preparing the high-rate lithium nickel manganese oxide material with high entropy doping site design and modification according to claim 1, characterized in that: The specific process of sintering is: increase the temperature to the pre-firing temperature at a heating rate of 0.5-10°C / min, the pre-firing temperature is 450-550°C, the pre-firing time is 4-6h, then increase the temperature to the sintering temperature at a heating rate of 0.5-10°C / min, the sintering temperature is 750-950°C, the sintering time is 8-15h, and cool down to room temperature at a cooling rate of 0.5-2°C / min.
9. A high-rate lithium nickel manganese oxide material with a high entropy doping site design and modification prepared according to the method of any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a separator located between the positive electrode and the negative electrode, wherein the positive electrode is prepared by using the high-rate lithium nickel manganese oxide material modified by the high entropy doping site design as claimed in claim 9.
Citation Information
Patent Citations
High-entropy ceramic modified positive electrode material and preparation method and application thereof
CN115050940A
High-entropy alloy modified high-nickel cobalt-free positive electrode material and preparation method thereof
CN117059795A
Preparation method and application of multi-element bulk phase doped and modified lithium nickel manganese oxide positive electrode material
CN118771468A
Cited By
Preparation method of lithium nickel manganese oxide positive electrode active material, battery monomer, battery device and power utilization device
CN120809813A
Lithium ion secondary battery, positive electrode active material, preparation method and electric equipment
CN121215860A